(untitled) (Medico Legal Update, 2020)
Background/Objectives: The purpose of this study is to identify the influencing factors of fine particle concentration levelby region and health behaviors on suicide attempts. Method/Statistical Analysis: This study used the 7th (2016-2017) primitive data disclosed by the National Health Nutrition Examination Survey. Considering the design features of the sample data, it is analyzed with a complex sampling method by reflecting stratas, clusters, and weight. The data were analyzed using logistic regression analysis of the complex sampleusing the SPSS/WIN 18.0 program. Findings: As a result of logistic regression analysis, the provability of suicide attempt was 12.32 times (95% CI 5.33-28.49, p<.001) higher in depression diagnosis group, 5.55 times (95% CI 1.87-16.46, p=.002) higher in 10 or more drinks in single session group, 2.48 times (95% CI 1.07-5.73, p=.003) higher in high perceived stress group, and 0.1 unit increase in Health-related Quality of life (? = -2.35, p=.030) resulted in 0.79 times factor on suicide attempt rate. Improvements/Applications: This study can provide basic data to develop an intervention program that can reduce suicide attempt rate by analyzing environmental and health related factors affecting suicide attempts.